Long-term outcomes of systemic therapies for Hurler syndrome: an international multicenter comparison. (November 2018) - Eisengart, Julie; Rudser, Kyle; Xue, Yong; Orchard, Paul; Miller, Weston; Lund, Troy; Van der Ploeg, Ans; Mercer, Jean; Jones, Simon; Mengel, Karl Eugen; Gökce, Seyfullah; Guffon, Nathalie; et al.
Abstract Purpose Early treatment is critical for mucopolysaccharidosis type I (MPS I), justifying its incorporation into newborn screening. Enzyme replacement therapy (ERT) treats MPS I, yet presumptions that ERT cannot penetrate the blood–brain barrier (BBB) support recommendations that hematopoietic cell transplantation (HCT) treat the severe, neurodegenerative form (Hurler syndrome). Ethics precludes randomized comparison of ERT with HCT, but insight into this comparison is presented with an international cohort of patients with Hurler syndrome who received long-term ERT from a young age. Methods Long-term survival and neurologic outcomes were compared among three groups of patients with Hurler syndrome: 18 treated with ERT monotherapy (ERT group), 54 who underwent HCT (HCT group), and 23 who received no therapy (Untreated). All were followed starting before age 5 years. A sensitivity analysis restricted age of treatment below 3 years. Results Survival was worse when comparing ERT versus HCT, and Untreated versus ERT. The cumulative incidences of hydrocephalus and cervical spinal cord compression were greater in ERT versus HCT. Findings persisted in the sensitivity analysis. Conclusion As newborn screening widens treatment opportunity for Hurler syndrome, this examination of early treatment quantifies some ERT benefit, supports presumptions about BBB impenetrability, and aligns with current guidelines to treat with HCT.